2011
DOI: 10.1016/j.jacc.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 Is a New Inflammatory Marker Correlated With Left Ventricular Diastolic Dysfunction and Heart Failure With Normal Ejection Fraction

Abstract: Pentraxin 3 is significantly elevated in HFNEF patients and produced in the coronary circulation in patients with LVDD. Pentraxin 3, but not high-sensitivity CRP, is an independent inflammatory marker correlated with the presence of LVDD and HFNEF. (The Clinical Significance of Plasma Pentraxin 3 levels for Patients with Diastolic Heart Failure; UMIN000002170).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
131
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 10 publications
6
131
1
11
Order By: Relevance
“…Left atrial volume index is a relatively robust measure of diastolic function as it is less acutely load‐sensitive than various Doppler derived indexes. The correlation between PTX3 and left atrial volume may be related to the fact that this relatively recently described biomarker has a strong association with myocardial fibrosis and, consistent with the endothelial inflammation hypothesis, is strongly expressed by vascular endothelium 21, 22, 23, 53. Whether PTX3 truly has a specific pathophysiologic role in HF is not known.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Left atrial volume index is a relatively robust measure of diastolic function as it is less acutely load‐sensitive than various Doppler derived indexes. The correlation between PTX3 and left atrial volume may be related to the fact that this relatively recently described biomarker has a strong association with myocardial fibrosis and, consistent with the endothelial inflammation hypothesis, is strongly expressed by vascular endothelium 21, 22, 23, 53. Whether PTX3 truly has a specific pathophysiologic role in HF is not known.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, the contribution of a pro‐inflammatory state to the pathophysiology of HFpEF has been emphasized 6, 8, 17, 23, 31, 34, 35, 36, 45. In patients with ADHF, biomarkers reflecting activation of the renin‐angiotensin aldosterone system (RAAS) (plasma renin activity, aldosterone levels), oxidative stress (uric acid) and collagen synthesis (N‐terminal procollagen III) appear to be elevated to a similar extent in HFrEF and HFpEF 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings accentuate the role inflammation plays in both female HFpEF and pre‐eclampsia and suggest the possible use of C‐reactive protein in cardiovascular risk screening in pregnancies complicated by hypertension. The inflammatory component of HFpEF has been mentioned previously,10, 101 with for example IL‐6, TNF‐α, interleukin receptors, and pentraxin 3 as potential HFpEF biomarkers 10, 102, 103, 104, 105. To our knowledge, gender‐specific data on this topic are currently lacking; thus with our women‐only designed search, we probably overlooked a number of studies on inflammatory markers in HFpEF.…”
Section: Discussionmentioning
confidence: 97%
“…According to certain authors, PTX3 may have a prognostic role in HF. Matsubara et al [5] demonstrated that PTX3 is an independent marker of left ventricular (LV) diastolic dysfunction in HF with preserved ejection fraction (EF), and that myocardium may contribute to increased concentration of this protein in the blood.…”
Section: Introductionmentioning
confidence: 99%